The Role of Forecasting in Managerial Planning: A Literature Review of Methods, Contributions, and Implementation Challenges - Made Diah Kartika Maharani (The Journal of Financial, Accounting, and Economics, 2026)
The increasingly dynamic, complex, and uncertain business environment demands that organizations have the ability to anticipate various possible future conditions as a basis for planning and decision-making. In this context, forecasting plays a crucial role as a managerial support instrument that enables organizations to utilize historical data, patterns, trends, and relevant information to generate estimates of future conditions. This study aims to analyze the role of forecasting in managerial planning, identify forecasting methods used in business practices, analyze their contribution to the effectiveness of planning and decision-making, and identify challenges in their implementation. The study uses a literature review approach by examining various relevant academic literature on forecasting, forecasting methods, business planning, managerial decision-making, and the use of technology in forecasting. The literature is analyzed descriptively, comparatively, and interpretively by linking various research findings to gain a more comprehensive understanding. The study results show that forecasting serves as a supporting instrument for strategic, operational, and financial planning by providing information about possible future conditions. Forecasting methods can be grouped into quantitative approaches, such as time series, moving averages, exponential smoothing, ARIMA, regression, and Monte Carlo simulations, and qualitative approaches such as the Delphi method, scenario planning, and market research. No single method is universally superior because forecasting effectiveness depends on data characteristics, forecasting objectives, time horizon, level of uncertainty, and organizational context. Forecasting can improve the quality of resource planning, risk management, inter-unit coordination, and financial planning, but it does not automatically produce correct decisions. Its effectiveness is also influenced by data quality, human resource competency, model selection, organizational culture, technological support, and management's ability to interpret and use prediction results. Therefore, an integrative approach that combines quantitative and qualitative methods, supported by technology, human resource competency, and continuous model evaluation, is essential to enhancing the benefits of forecasting in managerial planning.